Injectable MXene/Ag-HA composite hydrogel for enhanced alveolar bone healing and mechanistic study - Li, Jialing; Fan, Zilu; Guan, Zhenju; Ruan, Jianping (Frontiers in Bioengineering and Biotechnology, 2024)
Alveolar bone defects are common challenges in dentistry. Due to the complexity of alveolar bone anatomy and insufficient repair mechanisms, large bone defects are difficult for the body to heal on its own, and clinical treatment typically involves the use of bone substitute materials. However, current substitutes often have limitations such as insufficient osteoinductivity, rapid degradation, inflammatory responses, and poor mechanical properties. Additionally, the irregular morphology of alveolar bone defects complicates the use of solid bone substitutes, potentially leading to secondary damage at the repair site. This study presents an innovative approach by integrating MXene nanomaterials, renowned for their excellent biocompatibility, antibacterial properties, and mechanical strength, into Ag-HA/GelMA hydrogels to create an injectable MXene/Ag-HA composite hydrogel. The results indicate that this composite hydrogel exhibits satisfactory mechanical and biological properties, especially excelling in antibacterial, antioxidant, and osteogenic activities. Gene expression analysis reveals that the MXene composite hydrogel promotes osteogenesis by regulating the expression of Dmp1 and Dusp1, prompting it a promising candidate for alveolar bone repair and regeneration, and further demonstrating the vast potential of MXene nanomaterials in the biomedical field.